Evaluation of the Worksheets Based on Six Thinking Hats and Case Study according to Critical Thinking Skills: Heat and Temperature - Çiğdem Şahin; Nuray Çakmak (Journal of the Turkish Chemical Society Section C Chemical Education, 2016)
The aim of this study was to examine the effect of worksheets based on six thinking hats and case study on improvement of prospective science teachers’ critical thinking skills in a comparative manner. This study was designed on case study research method. The working group composed of 24 prospective science teachers who were studying at the 3th grade at the Elementary Department Science Teacher of Education Faculty in Giresun University. In the study, worksheets and journals were used for collecting data. Data obtained from worksheets based on six thinking hats and case study and journals were analyzed to document review technique. Qualitative data of the study about prospective science teachers’ critical thinking skills were analyzed with sub-factories of California Thinking Disposition Inventory (CCTDI) which was translated to Turkish by Kökdemir (2003) as descriptively. Qualitative data of both worksheets and journals of this study showed that although prospective science teachers generally stated with respect to analyticity and truth-seeking sub factories of critical thinking skills, they did not state about self-confidence and inquisitiveness sub factories.